Post-streptococcal acute glomerulonephritis in a 7-year-old boy: Islamic perspective on the prevention of the disease - Mohd Tharmizi, Siti Nursyahirah; Md A Azila, Nur Zulfiqar; Kardani, Astrid Kristina; Bahbah, Mohammad Nasser Hamed Mahmoud; Hasan, Taufiq Hidayat (2016)
Introduction: Acute glomerulonephritis is inflammation of the kidney mediated by an immunological process. Group A β-haemolytic streptococcal infection is common in children aged 5-12 years old and can lead to acute post-streptococcal glomerulonephritis which may develop after recovery from a streptococcal throat infection or skin infection (impetigo). 97% of cases occur in less developed country. The incidence has decreased in industrialized nations due to improved hygienic condition. Case Report: A 7-year-old boy, the eldest child of 4 siblings from a divorced parent, was admitted to Hospital Tengku Ampuan Afzan Kuantan in March 2015 due to facial puffiness for 1 day duration. There was also dark colored urine. Patient had history of productive cough for 3 days and fever for 2 days. Father also complained of skin ulcer on patient’s right feet for about 1 month. There was hypertension (198/80 mmHg). Urine examination showed hematuria, proteinuria, and leucocyturia. Anti-streptolysin O titre was high (1:800) and complement C3 level was low (0.29). Patient was treated with antibiotic, diuretic, and anti-hypertension. Discussions: The child is entrusted to the parents who will be called by the Almighty, who will ask them about this trust. Parents plays vital role in maintaining and promoting the good health of the children. Parents should also pay attention to cleanliness, personal hygiene and the prevention of disease, especially infection. Islam paid attention to washing hand and cleansing the air inhaled into the lungs by regular cleaning of the nose as part of ablution before performing prayer. Conclusions: Parents are responsible in preserve life, health and growth of their children. Caring for cleanliness and hygiene is not only deemed a good habit in Islam but also rendered into rituals that constitute part of the faith itself.